New scheme in determining nth order diagrams for cross multiplication method via combinatorial approach - Karim, Sharmila; Ibrahim, Haslinda; Omar, Zurni (World Academy of Science, Engineering and Technology, 2011)
In this paper, a new recursive strategy is proposed for determining (n-1)!/2 of nth order diagrams.The generalization of nth diagram for cross multiplication method were proposed by Pavlovic and Bankier but the specific rule of determining (n-1)!/2 of the nth order diagram for square matrix is yet to be discovered.Thus using combinatorial approach(n-1)!/2 of the nth order diagrams will be presented as (n-1)!/2 starter sets. These starter sets will be generated based on exchanging one element. The advantages of this new strategy are the discarding process was eliminated and the sign of starter set is alternated to each others.